Multicentre study of abdominal aortic aneurysm measurement and enlargement. Issue 12 (2nd September 2015) - Lederle, F A; Noorbaloochi, S; Nugent, S; Taylor, B C; Grill, J P; Kohler, T R; Cole, L
Abstract: Background: No effective treatment is currently available to prevent progression of small and medium-sized abdominal aortic aneurysms (AAAs). Identification of drugs with sufficient promise to justify large expensive randomized trials remains challenging. One potentially useful strategy is to look for associations between commonly used drugs and AAA enlargement in appropriately adjusted observational studies. Methods: Potential AAA measurements were identified from abdominal imaging reports in the electronic data files of three medical centres from 1995 to 2010. AAA measurements were extracted manually and patients with an aneurysm of 3 cm or larger, who had at least two measurements over an interval of at least 6 months, were identified. Other data were obtained from the electronic data files (demographics, co-morbidities, smoking status, drug use) to conduct a propensity analysis of the associations of drugs and other factors with AAA enlargement. Results: From 52 962 abdominal imaging studies, 5362 patients with an AAA of 3 cm or more were identified, of whom 2428 had at least two measurements over at least 6 months. Mean AAA follow-up was 3·4 years and the mean AAA enlargement rate was 2·0 mm per year. Propensity analysis demonstrated no significant association of AAA enlargement with statins, beta-blockers, angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers. Diabetes was associated with a reduction in AAA enlargement of 1·2 mm per year ( P = 0·008), and chronic obstructive pulmonary disease was associated with increased enlargement (0·5 mm per year; P = 0·050). Moderate AAA measurement variation and substantial terminal digit preference were also observed, but the digit preference became less pronounced after 2000. Conclusion: This study confirms the negative association of diabetes with AAA progression. There was no evidence that commonly used cardiovascular drugs affect AAA enlargement. Abstract : Nothing to reduce growth